2015
DOI: 10.15438/rr.5.4.126
|View full text |Cite
|
Sign up to set email alerts
|

New Instrumentation Reduces Operative Time in Medial Unicompartmental Knee Arthroplasty Using the Oxford Mobile Bearing Design

Abstract: Redesigned instrumentation has become available for implantation of the Oxford Mobile Bearing Medial unicompartmental knee arthroplasty. To assess the benefit of these changes, we compared operative time of 200 Phase III and 176 Microplasty UKA done 2008-2011. An average time savings of 8.6 minutes was seen with the Microplasty design.  Additionally, the standard deviation in operative times, minimum and maximum operatives were lower in knees in which Microplasty instrumentation was utilized.  A 15% savings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, a p -value of < 0.05 allowed us to reject the null hypothesis and indicated equivalence (i.e., that the two positioning types are the same). Using extant research and clinical experience, d-values were prespecified for procedure time, 10 tibial and femoral alignment, 11 arc of motion, 12 laxity, 13 and fractures ( Table 1 ). For learning ability or time for individual steps of the cases, d-values were set to the smallest values for which resources were available to study an effect.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a p -value of < 0.05 allowed us to reject the null hypothesis and indicated equivalence (i.e., that the two positioning types are the same). Using extant research and clinical experience, d-values were prespecified for procedure time, 10 tibial and femoral alignment, 11 arc of motion, 12 laxity, 13 and fractures ( Table 1 ). For learning ability or time for individual steps of the cases, d-values were set to the smallest values for which resources were available to study an effect.…”
Section: Methodsmentioning
confidence: 99%
“…The 3-year re-revision rates were 8.4% (CI 4. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] after conversion to TKR for failed Microplasty and 11% (CI 7. [8][9][10][11][12][13][14][15] for failed non-Microplasty instrumented PKRs with a hazard ratio of 0.77 (CI 0.36-1.7).…”
mentioning
confidence: 99%
“…Microplasty instrumentation for the Oxford Mobile Partial Knee (Zimmer Biomet, Warsaw, IN, USA), was introduced as having a more consistent implant position and more accurate and bone -preserving tibial resection [8]. Recent results demonstrated improved implant position with reduced operation times using Microplasty instrumentation [9][10][11][12]. A recent group-matched registry study showed a 40% decrease in revision rate of PKRs instrumented with Microplasty (3.3% vs. 5.5%) [13].…”
mentioning
confidence: 99%